Processing‐Dependent Microstructure of AgCl–CsAgCl2 Eutectic Photonic Crystals. Issue 14 (7th May 2018) - Choi, Jaewon; Kulkarni, Ashish A.; Hanson, Erik; Bacon‐Brown, Daniel; Thornton, Katsuyo; Braun, Paul V.
Abstract: Directional solidification of a eutectic melt allows control over the resultant eutectic microstructure, which in turn impacts both the mechanical and optical properties of the material. These self‐organized phase‐separated eutectic materials can be tuned to have periodicities from tens of micrometers down to nanometers. Furthermore, the two phases possess differences in their refractive index leading to interesting optical properties that can be tailored within the visible to infrared wavelength regime. It is found the binary salt eutectic AgCl–CsAgCl2 system forms a rod microstructure with sample draw rates up to 0.2 mm s −1 which transitions to a lamellar microstructure at draw rates greater than 0.36 mm s −1 . Heat‐transfer simulations reveal a draw rate‐dependent direction of motion of the solidification front, which for a range of draw rates requires nucleation of the minority solid phase at the sample wall. Phase‐field modeling indicates that the initial eutectic structure at the sample boundary, either rod or lamellar, dictates the bulk eutectic morphology. These samples contain submicrometer periodicities which coupled with their optical transparency results in them exhibiting draw rate‐dependent near‐IR reflectance peaks consistent with stop bands for 2D hexagonal (rod) and 1D planar (lamellar) photonic crystals. Abstract : The eutectic composition of the molten salts AgCl and CsCl exhibits a microstructural transition from rod to lamellar upon varying the draw rates controlled by directional solidification. This transition is dominated by the initial formation at the surface of either the rod or lamellar structure. The resultant eutectic microstructures have optical properties consistent with their being 2D and 1D photonic crystals.